Leading a change process to improve health service delivery - Bahamon Claire; Dwyer Joseph; Buxbaum Ann (The World Health Organization, 2006)
In the fields of health and development, donors channel multiple resources into the design of new practices and technologies, as well as small-scale programmes to test them. But successful practices are rarely scaled up to the level where they beneficially impact large, impoverished populations. An effective process for change is to use the experiences of new practices gained at the programme level for full-scale implementation. To make an impact, new practices need to be applied, and supported by management systems, at many organizational levels. At every level, potential implementers and likely beneficiaries must first recognize some characteristics that would benefit them in the new practices. An effective change process, led by a dedicated internal change agent, comprises several well-defined phases that successively broaden and institutionalize the use of new practices.